The Current Status of Baculovirus and Their Implication for Insect Pest Control - Arman Wijonarko (Universitas Gadjah Mada, 2001)
Baculovirus have been promoted as the promising bioinsecticides for their pest control potential for more than half a century. But only a few have been successful as biological control agent, and almost none has been proven as commercial success, or widely used for large-scale insect pest control. The bioinsecticides currently represent only a small fraction of the world pesticide market. The successful of the Bt crop marked a special achievement in the bioinsecticide market growth. How about the baculoviruses? The main hurdle for baculovirus to be developed as bioinsecticide is its poor performance compare to synthetic chemical ones, include the speed of kill, and host range. It is important to understand the nature of baculovirus, and explore the possibilities to develop new way in applying the baculovirus as bioinsecticides.